Tabebuia rosea (Bertol.) DC. ethanol extract attenuates body weight gain by activation of molecular mediators associated with browning. (November 2021) - Pagaza-Straffon, Elsa Cecilia; Mezo-González, Carla Elena; Chavaro-Pérez, David Armando; Cornejo-Garrido, Jorge; Marchat, Laurence A.; Benítez-Cardoza, Claudia G.; Anaya-Reyes, Maricruz; Ordaz-Pichardo, Cynthia
Graphical abstract: Highlights: T. rosea ethanol extract produced a significant decrease in body weight in high fat diet-induced obese C57BL/6 mice. T. rosea ethanol extract attenuates liver steatosis. T. rosea ethanol extract contains glycosylated coumarins, sterols, lapachol and quercetin. T. rosea ethanol extract has antioxidant capacity. T. rosea ethanol extract is not mutagenic, nor genotoxic, and did not show acute or repeated doses toxicity. Abstract: Tabebuia rosea has been reported to have anti-cancer, antioxidant, and hypoglycemic activities, and other species of the same genus have anti-obesity effect. Ethanol extract of T. rosea (TrEtOH) produced a significant decrease in body weight (12.1%), and a diminution in lipid profile markers in high fat diet-induced obese C57BL/6 mice. A reduction in the number of hypertrophic adipocytes and a decrease of triglycerides was observed in adipose tissue, added to a reduction in size and fat in hepatocytes. The administration of TrEtOH leads to the mRNA overexpression of UCP1, TBX1, and GLUT4, suggesting that the extract promotes adipocyte browning as a possible mechanism of action. A glycosylated coumarin, lapachol and quercetin were quantified in TrEtOH extract. Interestingly TrEtOH extract did not show mutagenicity, genotoxicity, or toxic effects after acute or 28 days repeated administration. TrEtOH extract could be used for the development of new drugs against obesity and its comorbidities.